Fabricating modern societies : education, bodies, and minds in the age of steel - Priem, Karin; Herman, Frederik (Studies in global social history,, 2019)
"Fabricating Modern Societies: Education, Bodies, and Minds in the Age of Steel, edited by Karin Priem and Frederik Herman, offers new interdisciplinary and transnational perspectives on the history of industrialization and societal transformation in early twentieth-century Luxembourg. The individual chapters focus on how industrialists addressed a large array of challenges related to industrialization, borrowing and mixing ideas originating in domains such as corporate identity formation, mediatization, scientification, technological innovation, mechanization, capitalism, mass production, medicalization, educationalization, artistic production, and social utopia, while competing with other interest groups who pursued their own goals. The book looks at different focus areas of modernity, and analyzes how humans created, mediated, and interacted with the technospheres of modern societies"--